Kritik Wacana Tafsir Dalam Dakwah Kontemporer: Isu-Isu dan Strategi Dakwah Kontemporer - Zamroni Wafa; Sadari; Asep Maskur (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This research aims to find out how contemporary issues related to religion as well as a challenge for Islamic da'wah, such as secularism, religious pluralism, liberal Islam (religious liberalism), radicalism-terrorism, and so on. The type of research used in this study uses a descriptive-qualitative library research approach, with the primary source being several references related to contemporary da'wah, while additional (secondary) sources and several references in the form of journals, books, and online media as supporting data that correlate with the focus of research. The results of this study indicate that Islam and its people, who are in the vortex of global currents and related to some contemporary issues, should come to the surface with contemporary Islamic ideas or thoughts to answer the challenges of da'wah while positioning Islam as a universal religion. Contemporary Islamic thought is thought to bridge two poles between tradition and modernity (al-turāts wa al-Hadassah) to raise new awareness and give birth to ideas that can respond to contemporary problems. Recommendations for further research with this research are expected to add insight related to contemporary issues.